1990
DOI: 10.1111/j.1365-2796.1990.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Salt resistant lipase activity in human adrenal gland is increased in Cushing's disease

Abstract: Salt resistant lipase (also designated hepatic lipase) is present in normal human adrenal cortex at activity levels of about 1 mU g-1 tissue wet weight. In hyperplastic adrenocortical tissue from four patients with Cushing's disease the salt resistant lipase activity was found to be about 5-fold higher than this value. The activity of salt resistant lipase in postheparin plasma was elevated in two of the patients, indicating that the high enzyme activity in adrenal cortex may originate from the liver. Lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(3 reference statements)
2
2
0
Order By: Relevance
“…Here, we show for the first time that full-length HL mRNA is expressed in the hyperplastic adrenals of patients with Cushing's disease. These adrenals are activated by increased pituitary secretion of ACTH, and contain elevated levels of HL activity (30,31). We corroborated these findings by promoter-reporter assays using the human adrenocortical NCI-H295R cell line.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Here, we show for the first time that full-length HL mRNA is expressed in the hyperplastic adrenals of patients with Cushing's disease. These adrenals are activated by increased pituitary secretion of ACTH, and contain elevated levels of HL activity (30,31). We corroborated these findings by promoter-reporter assays using the human adrenocortical NCI-H295R cell line.…”
Section: Discussionsupporting
confidence: 73%
“…In HL-null mice, the ACTH-induced increase in plasma corticosterone levels was attenuated, suggesting that adrenal HL is important for steroidogenesis (34). In patients with Cushing's disease, adrenal HL activity is severalfold higher than in controls (30,31), and the daily cortisol production is increased in parallel (30). Taken together, these observations strongly suggest that adrenal HL has an important role in cholesterol supply for steroid production (34).…”
Section: Discussionsupporting
confidence: 56%
“…We have previously shown that patients with pituitary Cushing's disease (endogenous ACTH overproduction) exhibit a fivefold increase in HL activity of adrenal tissue [6]. The present experiment was undertaken to determine the way in which ACTH affects HL activity in human liver.…”
Section: Introductionmentioning
confidence: 95%
“…LPL is the enzyme that hydrolyses the bulk of triacylglycerols carried in larger apolipoprotein Bcontaining lipoproteins such as chylomicra and very low density lipoprotein. It has been reported that H-type lipase activity is increased in rat adrenals after ACTH treatment and in humans with Cushing's disease (Jansen, Schoonderwoerd, Baggen & de Greef, 1983;Berg, Hansson & Nilsson-Ehle, 1990). -type lipase is present mainly in the liver (Semenkovich, Chen, Wims et al 1989), but in the rat the enzyme protein has also been demonstrated in adrenals and ovaries (Jansen & de Greef, 1981).…”
Section: Introductionmentioning
confidence: 99%